Association between COMMD1 gene polymorphism rs11125908 and rheumatoid arthritis in the Cuban population - M. Carpio Alvarez; A. Cintado Benitez; T. Diaz Argudin; H. Nodarse Cuni; M.d.C Dominguez Horta; J.R. Fernández Massó (Reumatismo, 2024)
Objective. To evaluate the association of the rs11125908 polymorphism in the COMMD1 gene in the Cuban population with rheumatoid arthritis (RA).